Features of melting high-chromium flux-cored wire in pulsed arc welding. Issue 1 (June 2021) - Davydov, Yuri; Korobov, Yuri; Davydov, Alexander
Abstract: The results of studies of the process of pulse-arc surfacing with flux-cored wire are presented. It is shown that with pulsed arc control, it is possible to increase the main parameters of the process to the values characteristic of a solid wire. The difference between the melting character of flux-cored and solid wire is shown.